Dissolved organic carbon dynamics in tallgrass prairie streams - Higgs, Sophie Alexandra (Kansas State University, 2018)
Contrary to the previous notion that a stream acts primarily as the transporter of materials from land to oceans, research has shown that in-stream processing of organic matter and nutrients is significant and relevant at a global scale. Dissolved organic carbon (DOC) is the most abundant form of organic carbon in streams and has been demonstrated as an important source of energy supporting stream food webs. Understanding the dynamics of DOC in streams is, therefore, important in determining the contribution of flowing waters to global carbon storage and release. However, DOC exists as many different compounds, varying in source, composition, and quality. The composition of DOC that ends up in streams is partly controlled by the surrounding watershed, and landscape effects on DOC quality and quantity in streams have been observed. In the North American Tallgrass prairie, woody encroachment has led to changes in riparian vegetation, potentially altering the DOC received by the stream, and making it important to understand rates of DOC transformation as landscape alterations continue. The heterogeneity of the DOC pool makes it difficult to fully describe its components and to measure transformation rates. DOC uptake, or biological use, has been estimated through several methods including in-stream additions of various DOC sources and bottle incubations of stream water and sediments. One problem with addition methods for calculating uptake is that the DOC pool is difficult to replicate and additions of simple compounds or organic leachates do not represent total dissolved organic carbon (TDOC) dynamics. Another potential issue is that additions of a labile compound could potentially alter microbial activity through a priming effect and therefore distort ambient DOC uptake estimates. Finally, uptake parameters are mostly calculated assuming benthic uptake while recent studies have shown that planktonic uptake of DOC can also be significant. We conducted this study with these three considerations in mind. In the first chapter, we describe our use of in situ additions of glucose and bur oak leaf leachate in prairie stream reaches and concentrations of specific components to determine uptake dynamics of various specific DOC components, from a simple sugar to more complex plant compounds. We calculated uptake parameters of glucose and two different oak leaf components. We found that using glucose concentrations rather than TDOC concentrations, as has been done in previous studies, to measure uptake parameters resulted in higher uptake rates, indicating the importance of measuring the specific component added. Through leaf leachate additions, we found that an amino acid like component was consistently taken up faster than a humic-like component. The second chapter addresses the questions of uptake location and priming through a series of recirculating chamber incubations. We found that benthic uptake of leaf leachate was more important than that in the water column. Finally, elevated uptake of one leaf leachate component in the presence of glucose indicated a priming effect on microbial DOC uptake.
Keywords: Biogeochemistry; Dissolved organic carbon; Streams